Curriculum evaluation of Education Subject Using CIPP Curriculum Model: Higher Secondary Level in Pakistan - Asma, Shahzadi; Muhammad, Ilyas Khan; Mahar, Muhammad Ijaz (Institute for Excellence in Education & Research, 2024)
Curriculum evaluation is an integral part of the educational process. Most curricula in Pakistan have often remained static for extended periods, hindering progress. Limited research has been conducted on the process of curriculum development in Pakistan in general and on the curriculum of the Education subject at the higher secondary level in particular. The current study aims to fill this gap by evaluating the existing curriculum of the Education subject at the higher secondary level in Pakistan using the CIPP (context, input, process, and product) evaluation model developed by Stufflebeam (1971). The purpose of this evaluation is to identify possible strengths and weaknesses of the curriculum of Education subject in order to make necessary improvements. The population for the study consisted of teachers at higher secondary level. A sequential explanatory mixed methods study was designed. Total population sampling was used to select the teachers and data was collected through questionnaire. Descriptive statistics for quantitative data was applied. The findings show that the textbook was the sole source of the subject content and there did not seem alignment between the curriculum and the textbook. The existing curriculum evaluation aimed to provide valuable insights for curriculum revision, with the goal of enhancing the subject matter to foster student interest, creativity, and positive social attitudes. This research makes significant contribution to educational planners and textbook developers to design more effective and efficient curricula according to the needs of students.